A multi-group analysis of social media engagement and loyalty constructs between full-service and low-cost carriers in Hong Kong. (October 2018) - Lee, C.K.M.; Ng, K.K.H.; Chan, Hing Kai; Choy, K.L.; Tai, W.C.; Choi, L.S.
Abstract: This study investigates the factors that influence customer loyalty to full-service carriers and low-cost carriers in the Hong Kong airline industry. A hypothesis model is proposed to examine the relationship of various drivers of customer loyalty. In this study, engagement in social media was used to assess the effect of advertising, while the impacts of perceived service quality were considered to measure the effect on perceived value, and their impacts on customer satisfaction and loyalty. Three hundred and fifty-six questionnaires were distributed at the Hong Kong International Airport to collect data. The multi-group analysis was conducted to evaluate the hypothesis model with two groups of passengers. The results confirmed that social media engagement, perceived service quality, and perceived value have an incidental relationship to customer satisfaction. Media engagement and service quality are the strong predictors of attitudinal and behavioural loyalty in low-cost carriers. Interestingly, our findings show that the two groups of passengers have notable differences regarding loyalty construction, which adequately explain how passengers have different service expectations and needs. Highlights: Media engagement in loyalty model was presented to fit the airline industry. MGA was proposed to identify the loyalty constructs between groups. The key factors affecting the loyalty constructs in FSC and LCC are identified. An empirical study was conducted in Hong Kong.